Zinc Plating Using Mixed-Chloride Bath - Haque, lnam-ul-; Murshid, Misbah; Khan, Asim (Biological Sciences - PJSIR, 2007)
Zinc electrodeposition from mixed ammoni um chloride/potassi um chloride bath was carried out and the i nfluence of plati ng time on the rest potential, white rust and red rust was studied. The zinc plated mild steel specimens were divided into four categories: non-chromated , yellow-chromated, greenish-grey chromated and black-chromated zinc plated mild steel specimens. There is no effect of plating time on the rest potential. The time taken for white rust and red rust increased with i ncrease in plating time. Black-chromated zinc plated mi ld steel specimens have maximum corrosion resistance . The abrasion resistance of yellow-chromated zinc plated mild steel specimens was very poor. The appearance and adhesi on of the deposits were good